The Effect of Augmented Reality on Students' Motivation and Spatial Ability: A Literature Review from 2016-2020 - Silvi, Ika (Tauladan Fathimah Azzahra, 2022)
Student motivation in learning is one of the most important things during the learning process, lack of motivation makes students lazy and unmotivated during the learning process. On the other hand, with increased motivation, students will hone their ability to understand, remember and communicate the subject matter they get during the learning process or what is called spatial ability. The application of Augmented Reality in the learning process is expected to build students' motivation and spatial abilities. The development of technology is expected to make the learning process more interactive and communicative. In this literature review analysis, we will discuss the contribution of Augmented Reality to increasing students' motivation and spatial abilities during the learning process. twenty articles downloaded from springer database from 2016-2020. based on this literature review, the application of Augmented Reality to strengthen students' motivation and spatial abilities during the learning proces s